PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. KRESNA REKSA FINANCE CABANG SAMARINDA - Wahyudi, Wahyudi Wahyudi (EKONOMIA, 2019)
The Acceptance Accounting Information System and the Samarinda Branch Cash flow, under the guidance of Mrs. Titin Ruliana and Mrs. Rina Masithoh Haryadi. The purpose of this research is to design information systems for acceptance and flow at PT. Kresna Reksa Finance Samarinda Branch. In accordance with the purpose of this study, the main points raised are: (1) To know and release the application of the cash accounting information system at PT. Kresan Reksa Finance, (2) To find out and analyze the application of information systems at PT. Kresan Reksa Finance